Associations between oxygen saturation Index and oxygenation index in neonates with congenital diaphragmatic hernia - Ali, Kamal; Algarni, Saleh S.; Alotaibi, Abdullah M.; Aljuaid, Nemer; Ghazwani, Abadi; Alshreedah, Saad; Alotaibi, Naif; Alanazi, Ibrahim; Almutairi, Mashael; Althubaiti, Manal; Alsehli, Faisal; Alwatban, Ahmed; et al. (Frontiers in Pediatrics, 2024)
Objective: To explore the relationship between Oxygenation Index (OI) and Oxygen Saturation Index (OSI) among infants with Congenital Diaphragmatic Hernia (CDH), both within the first 24 hours after birth and in extended observations in those who survived until their surgical intervention.Method: Seven-years retrospective review of CDH cases at a single Level III neonatal intensive care unit. The correlations of various combinations of OI-OSI pairs were assessed using the Spearman's rho Correlation Coefficient. Additionally, during the initial 24 hours, the correlations between best (lowest), highest, and mean OI and OSI values were determined.The predictive ability of the first 24 hours OIs and OSIs for mortality and other adverse outcomes were assessed using the Area Under the Curve (AUC) analysis.: Thirty-seven infants with CDH were included in the analysis. A strong correlation was observed between all pairs of OI/OSI (2289) (Spearman's rho = 0.843), matched pairs of Postductal OI/OSI (1232 pairs) (Spearman's rho = 0.835) and the unmatched pairs of Postductal OI and Preductal OSI (1057 pairs) (Spearman's rho= 0.852). Using the regression equations for all pairs, matched and unmatched OI/OSI pairs, we deduced that for clinically pertinent OI thresholds of 10,15,20 and 40, the corresponding OSI values were 5, 8, 11, and 23, respectively.Furthermore, in the first 24 hours, strong correlations were evident between best OI/OSI (Spearman's rho=0.848), highest OI/OSI (Spearman's rho=0.921) and the mean OI/OSI (Spearman's rho of 0.928). First (AUC=0.849), best (AUC=0.927), highest (AUC=0.942) and mean day 1 OI (AUC=0.946) were all predictive of mortality. Similarly, first (AUC=1.00), best (AUC=0.989), highest (AUC=1.00) and the mean OSI in day 1 (AUC=0.978) were all predictive of mortality. All of the OIs and OSIs in day 1 except for the admission OSI (AUC=0.683) were predictive of pulmonary hypertension. Additionally, all of OI and OSI indices in the first 24-hour except for the best day 1 OI (AUC=0.674) were predictive of the need for rescue HFOV.There were a strong correlation between the OI and OSI in infants with CDH. Conclusion: Oxygenation indices and OSIs in the first 24 hours were predictive of mortality and other adverse outcomes in infants with CDH.